New Keynesian versus old Keynesian government spending multipliers - John F. Cogan; Tobias Cwik; John B. Taylor; Volker Wieland (European Central Bank (ECB), 2009)
Renewed interest in fiscal policy has increased the use of quantitative models to evaluate policy. Because of modelling uncertainty, it is essential that policy evaluations be robust to alternative assumptions. We find that models currently being used in practice to evaluate fiscal policy stimulus proposals are not robust. Government spending multipliers in an alternative empirically-estimated and widely-cited new Keynesian model are much smaller than in these old Keynesian models; the estimated stimulus is extremely small with GDP and employment effects only one-sixth as large.
Keywords: C52; E62; 330; fiscal multiplier; Fiscal Stimulus; government spending; Macroeconomic Modeling; New Keynesian Model; Finanzpolitik; Öffentliche Ausgaben; Keynesianismus; Multiplikator; Schätzung; USA